Déficit habitacional no Brasil: um exame da relação entre políticas habitacionais e financeirização do setor imobiliário - Souza,Victor Suursoo de (2024)
This dissertation addresses the persistent issue of housing deficit in Brazil, examining housing policies and their connection to the financialization of the real estate sector, as well as the impact on access to housing for low-income populations. The housing deficit is a measure that reflects the quantitative and/or qualitative inadequacy of the housing supply in relation to the population’s demand. The study emphasizes the relationship between the financialization of the real estate market and the housing deficit. The influence of neoliberalism on the financialization of the real estate market plays a crucial role, resulting in privatizations, regulatory flexibilities, and an increase in private financing, exacerbating the housing deficit and intensifying the gentrification process. The study also examines countercyclical policies in the construction sector, with a focus on the Minha Casa Minha Vida program launched in 2009, assessing its impacts on reducing the housing deficit, the quality of housing, and socio-environmental implications. The main findings underscore the significant impact of financialization on the Brazilian real estate market, exacerbating housing deficits and accentuating inequalities. The concentration on housing programs, such as Minha Casa, Minha Vida, proved to be limiting, highlighting the need for more decentralized approaches. The emergence of gentrification reflects a shift in housing policies’ priorities, favoring capital gains